(untitled) (Research, Society and Development, 2025)
Currently, Brazil is the world leader in beef exports. In view of this, this study aims to analyze the main factors that influence beef production in the finishing phase within the intensive system, highlighting nutritional strategies available in the current market with efficiency indexes, the choice of breeds and their impact on meat quality. A qualitative study and narrative review of the literature were carried out. Raising beef cattle in the finishing phase in confinement has shown great viability within the national scenario of beef cattle farming. Its performance has been growing and gaining recognition due to its advantageous economic and operational factors, justified by the better use and significant gain in carcass of confined animals in a relatively short period, consequent strategic and balanced feeding. As with any activity, this also has some challenges that are still difficult to adjust, therefore, it would be of great importance if there were more studies and research focused on this activity, triggering smarter options with lower financial costs so that profit has the deserved prominence.